THE DEVELOPMENT OF A NEW KA-BAND NEAR-FIELD PLANAR MEASUREMENT SYSTEM FOR A DIGITAL PHASED ARRAY RADAR - Moncada Calmet, Luis Felipe (My University, 2024)
A near-field planar scanner is an electromechanical system whose objective is to obtain the far-field pattern of a mostly directive antenna by recording its electromagnetic fields in the near-field region by taking measurements at different points on an imaginary finite plane in front of the antenna under test, the collected data are then mathematically processed to obtain the far-field patterns. Near-field planar scanners are an excellent solution to the various limitations involved in far-field measurement. This type of system does not require an extremely large anechoic chamber to avoid external and self-interference in a controlled environment and does not require the AUT to rotate or move in any direction, making this system ideal for measuring array antennas. Currently the use of array antennas is proliferating, so the need for affordable systems to test and calibrate them is essential. The objective of this thesis is to provide the design and assembly steps of a low-budget, customizable, open-source near-field planar scanner. This thesis discusses the mathematical equations and theoretical foundations of near-field planar scanners. It also explains our proposed hardware and software design, highlighting the most important considerations. This work also discusses the process to perform an antenna measurement using the present system taking advantage of all its capabilities and finally, this thesis presents the accuracy and correct operation of the proposed scanner.
Keywords: Near-field planar scanner; Antenna measurements; Near-field to far-field transformation